last day (15 days later) » 

10:49
-4
Q: Can you disprove $1=2$

AhanProblem: Is $1=2$? A. We know that $e^{i\pi}=-1$ $$\begin{align} & \implies -e^{i\pi} & = 1 \\ & \implies -e^{i\pi} -e^{i\pi} & = 1 + 1 \\ & \implies -e^{i\pi}(1+1) & = 1 + 1 \\ & \implies -e^{i\pi}(-e^{i\pi} -e^{i\pi}) & = 1 + 1 \\ & \implies (-e^{i\pi})(-e^{i\pi})(1+1) & = 1 + 1 \\ & \implie...

I think $(-e^{i\pi})(-e^{i\pi})(-e^{i\pi})(-e^{i\pi})(-e^{i\pi}).. \ne (-e^{i\pi})(-e^{i\pi})(-e^{i\pi})(1+1)$.
The infinite product $(−e^{iπ})(−e^{iπ})(−e^{iπ})...$ does not exist.
I don't see why one could simply forget $(1+1)$ when "doing it infinitley"
user610551
There is no space for $(1+1)$ since there are infinite amount of $e's$.
When you write "There is no scope ...", what in the world do you mean?
10:49
If there's 'no scope' for $(1+1)$ then you can't "do it infinitely".
user610551
Have seen a problem that $x^{x^{x^x..}}=\sqrt 2$? we solve that by reversing $x^x=\sqrt 2$.
You should have written "We can do it infinitely. $$\implies(-e^{i\pi})(-e^{i\pi})\cdots(-e^{i\pi})(-e^{i\pi})(1+1)$$"
user610551
There is nothing more than infinite. Your explanation shows that there are infinite+$1$ terms.
How can $1+1$ implie $-e^{i\pi}-e^{i\pi}$? That logically doesnt make sense
@Ahan please read this: en.m.wikipedia.org/wiki/Statement_(logic) $1+1$ simply isnt even a statement
"Nothing more than infinite" is not quite right. Infinity has strange properties like, $\infty + 1 = \infty$ and when $c > 0, c\cdot \infty = \infty$ That still doesn't mean you can throw away factors which occur after $1^\infty $
10:49
The other commenters are trying to help you. First as tina mentions, you should be putting the equals to symbol between your equations, not implications. Second, you are making the erraneous step of assuming that you can't write the $(1+1)$ at the end because you have already infinitely many things before it. But consider the following : just bring that to the front just after D (since multiplication here is commutative). Then you have $(1+1)\times(\text{ a bunch of things })$.
user610551
@Tina $1 = -e^{i\pi}$. So, we can substitute. Substitute $+1$ for $-e^{i\pi}$. So, we get $+1+1$. We can ignore the plus of the left side $1$. So, $1+1$.
Just to drive home the point, we have the sum $1+1/2+1/4+1/8+\cdots$ and we can in fact do $(1+1/2+1/4+1/8+\cdots)+1$. This is completely valid. We just do it like $1$, then $1+1$, then $1+1/2+1$, then $1+1/2+1/4+1$ and so on.
@Tina That part is actually fine. $e^{i\pi}=-1 \implies -e^{i\pi}= 1$ so $-e^{i\pi} -e^{i\pi}= 1+1$
Hmmm, this may be the quickest I've seen a question closed.
For the record the problem is from step H to I.
user610551
@nickalh But, why?
user610551
That means infinity+1=infinity
user610551
10:49
But, that is not true.
Actually, it is.
user610551
Why does everyone giving me downvotes?
@nickalh but that is not what he writes. How can anything implie $-e^{i\pi}-e^{i\pi}$, that isnt even a mathematical statement.
user610551
I am not talking about statement. Just, they have to be equal.

last day (15 days later) »